2011
DOI: 10.1097/dcr.0b013e31822dd0f0
|View full text |Cite
|
Sign up to set email alerts
|

Determining Levels of Fecal Incontinence in the Community: A New Zealand Cross-Sectional Study

Abstract: This study helps to highlight some of the challenges involved with suitably identifying those who have fecal incontinence within the community. The prevalence rate of 13.2% represents a realistic measure of the burden of fecal incontinence in the general population, and further research in this area is recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
36
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 26 publications
1
36
1
1
Order By: Relevance
“…The prevalence of UI increases with age and is highly prevalent in the elderly and those with cognitive impairment [5]. Fecal incontinence (FI) occurs in up to 6% of those younger than 40 years increasing to 15% in older individuals [1, 2, 4]. Combined FI and UI has been reported in 10% of women and in 6–10% of men living in the community, increasing to almost 50% in nursing home residents [7–9].…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of UI increases with age and is highly prevalent in the elderly and those with cognitive impairment [5]. Fecal incontinence (FI) occurs in up to 6% of those younger than 40 years increasing to 15% in older individuals [1, 2, 4]. Combined FI and UI has been reported in 10% of women and in 6–10% of men living in the community, increasing to almost 50% in nursing home residents [7–9].…”
Section: Introductionmentioning
confidence: 99%
“…6,7 It is thought that prevalence may be underestimated because patients are often reluctant to report their symptoms. 8 Australian, 8 New Zealand, 9 Spanish, 10 and Korean 11 studies have reported prevalence rates of 15%, 12.4%, 10.8%, and 6.4% respectively, for random samples drawn from the general population. Although prevalence in women is thought to be higher than in men, 4 usually as a consequence of childbirth-related injuries, [12][13][14] some studies have failed to find clear epidemiological differences between the sexes, whereas other studies have actually reported higher prevalence rates for men than for women.…”
Section: Introductionmentioning
confidence: 99%
“…[1] AI results in emotional, psychological and social problems. [2][3][4] Mechanical sphincter disruption and nerve damage occurring as a complication of childbirth contribute to the development of AI. [2][3][4][5][6][7] Studies suggest that obstetric factors increase the risk of damage to the anal sphincter and subsequent development of AI.…”
mentioning
confidence: 99%
“…[2][3][4] Mechanical sphincter disruption and nerve damage occurring as a complication of childbirth contribute to the development of AI. [2][3][4][5][6][7] Studies suggest that obstetric factors increase the risk of damage to the anal sphincter and subsequent development of AI. [4][5][6] These include a prolonged second stage of labour, fetal macrosomia, posterior positions of the fetal skull, instrumental delivery, epidural analgesia, episiotomy and, most significantly, rupture of the anal sphincter.…”
mentioning
confidence: 99%
See 1 more Smart Citation